Perancangan Topologi Ring Dengan Spanning Tree Protocol Pada Jaringan Internet Area Perkantoran Bangko PT. Chevron Pacific Indonesia - Riski Ramadhani; Linna Oktaviana; Anhar Anhar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bangko Offices Area in PT. Chevron Pacific Indonesia require a network with reliability, stability, and efficiency to support the company. Currently, there are many problems that occur in today's network such as the link that was frequently interrupted, no backup paths in the network, and the speed of the link is still not uniform. Therefore, it is important to design a new network to solve that problem. In the new network design, used a ring topology plus additional backup lines, 1 Gbps bandwidth allocation, and the use of the spanning tree protocol. The design of the new network is done by using software OPNET Modeler with the parameters are delays and throughput. The needs of planning for next 5 years will be fulfilled with 1 Gpbs bandwidth alocation and the implementation of the spanning tree protocol will avoid loops and maintain network connectivity. With the new network design will be obtained a good Quality of Service with the network delays value corresponding to the category of delay and regularly use the service based on the priority determined. Keywords: network, bandwidth, spanning tree protocol, OPNET Modeler